Prolonged fever in a case of end stage renal disease with remained guidewire - mehrdad Jafari fesharaki; Mohammad Parsa Mahjoob; Naser Kachoueian; Vahid Eslami (International Journal of Cardiovascular Practice)
Central venous catheters,introduced for short-term dialysis,but occationally used as permanent vascular access in patient without alternative option. Hemodialysis(HD) patients presenting with fever have high rates of bacteremia,specially in patients with dialysis catheters and those with a history of bacteremia. [1]Herein,we report a case of end stage renal disease with catheter infection complicated with endocarditis